Electrostatic‐spray ionization mass spectrometry sniffing for perfume fingerprinting. (1st October 2013) - Tobolkina, Elena; Qiao, Liang; Xu, Guobin; Girault, Hubert H.
<x xml:space="preserve">Abstract</x> RATIONALE The perfume market is growing significantly, and it is easy to find imitative fragrances of probably all types of perfume. Such imitative fragrances are usually of lower quality than the authentic ones, creating a possible threat for perfume companies. Therefore, it is important to develop efficient chemical analysis techniques to screen rapidly perfume samples. METHODS Electrostatic‐spray ionization (ESTASI) was used to analyze directly samples sprayed or deposited on different types of paper. A linear ion trap mass spectrometer was used to detect the ions produced by ESTASI with a modified extended transfer capillary for 'sniffing' ions from the paper. RESULTS Several commercial perfumes and a model perfume were analyzed by ESTASI‐sniffing. The results obtained by paper ESTASI‐MS of commercial fragrances were compared with those obtained from ESI‐MS. In addition, a commercial fragrance was first nebulized on the hand and then soaked up by blotting paper, which was afterwards placed on an insulating plate for ESTASI‐MS analysis. Analysis of peptides and proteins was also performed to show that the paper ESTASI‐MS could be used for samples with very different molecular masses. CONCLUSIONS Paper ESTASI‐MS yields a rapid fingerprinting characterization of perfume fragrances, avoiding time‐consuming sample‐preparation steps, and thereby performing a rapid screening in a few seconds. Copyright © 2013 John Wiley & Sons, Ltd.